ANALISIS PENGEMBANGAN KOMBUCHA CASCARA PADA UD. MATT COFFEE DENGAN PENDEKATAN TRIPLE LAYERED BUSINESS MODEL CANVAS - Nindy Novianti Anggraeni; Rudi Wibowo (JSEP (Journal of Social and Agricultural Economics), 2021)
Kombucha cascara is a cascara innovation product at UD Matt Coffee was produced starting in 2018 as a new product, so a sustainable business model is needed. The objectivers of this study are to (1) make kombucha cascara business mapping at UD Matt Coffee with TLBMC approach and (2) determine the decision making on TLBMC kombucha cascara elements using Plus Minus Implication Analysis (PMIA) method. The method of determining research area using purposive method at UD Matt Coffee in Sukorejo Village, Sumber Wringin District, Bondowoso Regency. The method of determining the sample used was purposive sampling based on the specified criteria. The data analysis used was TLBMC and PMIA. The result showed that (1) The mapping business model of the kombucha cascara at UD Matt Coffee with TLBMC approach can be described as a whole in three integrated layers, such as economic layer, environmental layer, and social layer. (2) Decision making on TLBMC kombucha cascara elements using the PMIA method gives a total PMIA score in sequence started from higher to the lowes score, such as environmental layer +41, economic layer +38, and social layer +37, shows that UD Matt Coffee’s current decision making in development of kombucha cascara is appropriate and feasible to continue because it has paid attention to all elements in the economic, enviromental, and social layers which is sustainability oriented.